INDIKATOR SASARAN STRATEGIS AKUNTABILITAS KINERJA PEGAWAI - Ade Hermawan; Abd. Rohman (REFORMASI, 2022)
The government requires every government agency and work unit to compile accountability reports as a form of accountability. Therefore, it is necessary to develop and implement an appropriate, clear and tangible accountability system so that the administration of government at both the central and regional levels can be efficient, accountable and free from practices of corruption, collusion and nepotism (KKN). This study uses an evaluation method with a quantitative descriptive approach, with some respondents being State Civil Apparatuses who had received the services of the Personnel, Education and Training Agency (BKPP). The secondary data uses the Banjarbaru City BKPP performance report document. The information and facts obtained are then read, analyzed, and interpreted to draw conclusions. The results showed that the accountability of the performance of the Banjarbaru City BKPP was that the Performance Accountability of the Banjarbaru City Personnel, Education and Training Agency in general tended to be good as measured by two main indicators, namely the arrangement of personnel resources and the quality of personnel administration services. The indicator of the arrangement of personnel resources is measured using three items, namely the item apparatus that gets Competency Development, the position item that is filled in accordance with the competence, and the item apparatus that obeys the staffing regulations. AbstrakPemerintah mewajibkan setiap instansi pemerintah dan unit kerja untuk menyusun laporan akuntabilitas kinerjanya sebagai wujud pertanggung jawaban. Dari itu diperlukan pengembangan dan penerapan sistem pertanggung jawaban yang tepat, jelas dan nyata sehingga penyelenggaraan pemerintah baik tingkat pusat maupun daerah dapat berdaya guna, berhasil guna, dapat dipertanggung jawabkan dan bebas dari praktik korupsi, kolusi, dan nepotisme (KKN). Penelitian ini menggunakan metode evaluasi dengan pendekatan deskriptif kuantitatif dengan responden sebagian Aparatur Sipil Negara yang pernah mendapatkan pelayanan Badan Kepegawaian, Pendidikan dan Pelatihan (BKPP). Data skunder menggunakan dokumen laporan kinerja BKPP Kota Banjarbaru. Analisis data melalui tahapan mempelajari, menelaah dan menganalisa data. Hasil penelitian menunjukkan bahwa Akuntabilitas Kinerja Badan Kepegawaian, Pendidikan dan Pelatihan kota Banjarbaru secara umum cenderung baik yang diukur dengan dua indikator utama yaitu penataan sumber daya aparatur dan kualitas pelayanan administrasi kepegawaian. Indikator penataan sumber daya aparatur diukur dengan menggunakan tiga item, yakni item aparatur yang mendapatkan Pengembangan Kompetensi, item jabatan yang diisi sesuai dengan kompetensi, dan item aparatur yang taat terhadap peraturan kepegawaian.